Endogean and cavernicolous Coleoptera of the Balkans. XIV. Melledobythus bilandzijae, new genus and species of cavernicolous Bythinini (Staphylinidae: Pselaphinae) from the Island Mljet, Croatia - Hlaváč, Peter; Nakládal, Oto; Jalžić, Branko (Zootaxa, 2014)
Melledobythus bilandzijae, new cavernicolous genus and species of the tribe Bythinini is described from the island of Mljet, Croatia. A detailed morphological study is presented. The new genus belongs to the phylogenetic lineage of small and anophthalmous Bythinini that lack sutural elytral striae.